IDENTIFIKASI DAN TINGKAT KERUSAKAN OLEH SERANGGAPERUSAK PADA BIBIT SENGON (Falcataria moluccana) DI PERSEMAIAN PERMANEN BALAI PENGELOLAAN DAERAH ALIRAN SUNGAI DAN HUTAN LINDUNG KAPUAS PONTIANAK - Haerumi, Winda; Suryantini, Rosa; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2019)
Sengon is a fast growing tree species that can be harvested in a relatively short time, with a cropping rotation of around 5-8 years. This type is chosen as one of plant type industrial forest plantation in Indonesia, because it is able to adapt Â various types of soil. Sengon is a tree that is an alternative that can be cultivated extensively for rehabilitation purposes of marginal lands. Suplay of quality sengon seedlings is still constrained because there are destructive insect attacks.This study aims of was to identify insects that attack sengon seedlings and determine the level of damage caused by insects at permanent nursery areas BPDASHL Kapuas Pontianak. The method used in this study is a survey method with direct observation of sengon seedlings in the nursery area.The results of the studyÂ  found 8 types of destructive insect that attacks sengon seedlings (Falcataria moluccana) in the nursery area namely Eurema sp., Pteroma sp., Clania sp., Amatissa sp., Atractomorpha sp., Ferissia virgata, Valanga sp., and Conochepalus sp. The dominant insects species that attacks sengon seedlings in permanent nurseries are insects from the order Lepidoptera and non-dominant insects from order Orthoptera and Homoptera. The results showed that average percentage of destructive insect attacks is 23,33% and the average percentage the level of damage is 10% including is the low in the damage category.Keywords: destructive insects, identification, level of damage, permanent nursery, sengon seedlings